2012
DOI: 10.1111/1742-6723.12031
|View full text |Cite
|
Sign up to set email alerts
|

Intern underperformance is detected more frequently in emergency medicine rotations

Abstract: The prevalence of underperformance among interns is low, although higher than previously suggested. Emergency medicine detects relatively more interns in difficulty than other rotations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
1
11
1
Order By: Relevance
“…Assessors need to consider which of the 10 items are most important for monitoring development of the junior doctor and whether this differs for different clinical attachments. One recent study suggested that underperformance of junior doctors was more likely to be detected in emergency medicine rotations [18]. …”
Section: Discussionmentioning
confidence: 99%
“…Assessors need to consider which of the 10 items are most important for monitoring development of the junior doctor and whether this differs for different clinical attachments. One recent study suggested that underperformance of junior doctors was more likely to be detected in emergency medicine rotations [18]. …”
Section: Discussionmentioning
confidence: 99%
“…The sources of funding were as follows: five federal (two NIH, one Canada, and one Taiwan), five universitysponsored, two industry-supported, and two organizationally funded. Research methodology included 17 surveys (36%), 17,19,21,25,30,31,33,37,40,42,46,[50][51][52]54,60,61 15 (31%) observational analyses, [14][15][16]22,23,27,32,33,38,44,47,49,56,57,59 and three (6%) qualitative methodology studies. 19,28,45 There were only 12 (25%) with an experimental or quasi-experimental study design, 20,24,26,35,36,39,41,43,48,53,55,57 with five of the highlighted articles using this rigorous design.…”
Section: Trends In Medical Education Research In 2012mentioning
confidence: 99%
“…41,55 Each of the articles with a pediatric focus had the primary or supporting author with specialized pediatric training. Other prevalent subject areas with specialty author collaboration were psychiatry, 23,31,50,52,54 education, 15,16,18,20,33,34,36,57 and disaster medicine, 22,30,34,36,42 with all but one using simulation in their studies. Five articles (10%) this year evaluated tools that were developed for educational purposes 14,29,32,36,56 and learning methods were evaluated in eight articles (17%).…”
Section: Trends In Medical Education Research In 2012mentioning
confidence: 99%
“…10,15,16,21,24,29,30,33,36,38,39,42,46,47,49,50 Learner competence continued to be a prominent research topic, which was studied in 14 (33%) articles. 13,14,17,18,22,23,25,27,32,35,[43][44][45]50 Pediatric topics continued to be studied at about the same rate as in 2012, with seven (16%) articles. 18,21,25,33,37,40,48 Eleven articles (26%) evaluated learners' procedural competency.…”
Section: Trends In Medical Education Research In 2013mentioning
confidence: 99%